2004
DOI: 10.1038/sj.leu.2403480
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of children with newly diagnosed acute promyelocytic leukemia with arsenic trioxide: a single center experience

Abstract: A total of 11 children (five males and six females) with hypergranular type of acute promyelocytic leukemia (APML) were treated with intravenous arsenic trioxide (As 2 O 3 ) between December 1998 and October 2003. Eight cycles of As 2 O 3 (0.15 mg/kg/day) were administered (induction, consolidation and six cycles of maintenance) over a period of 12 months. The median WBC count at diagnosis was 3400/mm 3 (range: 800-9800). In all, 10 patients (91%) achieved hematological remission at a mean duration of 48 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 7 publications
1
47
0
Order By: Relevance
“…The differential treatment strategies for children with acute promyelocytic leukemia 40 and AML in DS 41 are clear examples of this approach. In addition, the role of new targeted drugs, such as gemtuzumab ozogamicin and FLT3 inhibitors, needs to be established by future clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…The differential treatment strategies for children with acute promyelocytic leukemia 40 and AML in DS 41 are clear examples of this approach. In addition, the role of new targeted drugs, such as gemtuzumab ozogamicin and FLT3 inhibitors, needs to be established by future clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…67 Recent literature supports our data in that the CR rate and EFS were relatively higher in the working groups using ATO/ATRA combination 68,69 compared with the groups using ATO alone. 59,60,62 GIMEMA group carried out a randomized phase III study to compare ATO þ ATRA versus standard ATRA þ anthracycline-based chemotherapy (AIDA regimen) for newly diagnosed non high-risk APL. We are eagerly anticipating their results.…”
Section: Induction Therapymentioning
confidence: 99%
“…(Mathews, et al 2010) This has also been piloted in 11 children, with similar encouraging findings. (George, et al 2004) When this is confirmed in larger studies treatment of APL without chemotherapy may be feasible, especially when no long-term toxicities from arsenic treatment emerge.…”
Section: Study Group Years No Of Patients Efs (5yrs) Os(5yrs) Referencesmentioning
confidence: 99%